Analítica dos sentidos e significados atribuídos por pessoas vivendo com insuficiência renal crônica em tratamento de hemodiálise: seus modos de ser-no-mundo/transcendência - Simone, Maria Cristina Longobardo (2011)
In times hypermodern, major advances in biotechnology are not yet sufficient to nullify all human suffering in adversity of the disease. The phenomenon of illness, given its complexity, involves conflicts in the dimensions physical, psychological, social, spiritual and existential. In the last decade, many studies have been concerned with the welfare of people living with chronic diseases. Many of these studies evaluate instruments through the quality of life for people with Chronic Renal Failure lifting quantitative aspects that suggest further elaboration. This gap in an attempt to engage with empirical data, this study aims to know the ways chosen to give meaning to illness and the meanings attributed by the person in daily life in hemodialysis treatment. In order to understand the direction of taking care of himself there, a man full of vision, a survey was conducted qualitative field phenomenological interviewing six adult participants who perform the renal replacement therapy at a private clinic in Sao Paulo. In-depth interviews were conducted with stimulating questions, for data analysis using the phenomenological reduction. In the analysis of the interviews the meaning of illness appears as ominous and uncontrollable. The responsibility for taking care of our own existence is transferred to another person pointing to lack of ownership and autonomy. In this direction, highlighted the ways of transcendence were religious coping, interpersonal relations and the ideal kidney transplant